Cor triatriatum sinister: Long‐term surgical outcomes in children and a proposal for a new classification. Issue 12 (2nd November 2022) - Mashadi, Ali H.; Narasimhan, Shanti L.; Said, Sameh M.
Abstract: Background: Cor Triatriatum Sinister (CTS) is a rare congenital anomaly with an estimated incidence of 0.4%, resulting from abnormal left atrial septation. It may present in isolation or in association with other heart defects. High percentage of patients require surgery with low mortality and recurrence rates. CTS has been classified in the past however we aim to describe a case series with more comprehensive and inclusive classification. Methods: This was a single‐center retrospective cohort study of 16 children with the diagnosis of CTS between 2000 and 2020. Medical records were reviewed for clinical presentations, hospital, and postoperative courses. Results: Sixteen patients (63% female), with a median age at diagnosis of 4.3 months, five (31%) were neonates. Six (38%) had isolated CTS, two (13%) with functional single ventricle (SV), and the remaining eight patients (50%) had other associated heart defects (septal defects in three, coarctation of the aorta in another three, and anomalous pulmonary venous connections in three). Eight patients (50%) presented with obstructed CTS. Twelve patients (75%) underwent surgical intervention. Mortality occurred in three patients (19%) with two surgical (one with total anomalous pulmonary venous connection and another with SV) and one nonsurgical (septal defect with Fanconi anemia). The surgical median follow up was 4.7 years. Recurrence of the membrane occurred in two patients (17%). Conclusions: This study showed good long‐term outcomes for patients with isolated and complex CTS. Complete and proper classification of CTS ensures appropriate diagnosis, surgical planning, and better family counseling which may correlate with outcomes.